Developing a Process Model for Future-Robust Advancement of Product Portfolios - Schlegel, Michael; Pommerer, Emily; Kempf, Christoph; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman; Albers, Albert (Proceedings of NordDesign 2024)

Methods and Approaches for Evaluating the Repairability of Mechatronic Systems: A Systematic Literature Review - Hermelingmeier, Dominik; Pape, Florian; Bunselmeyer, Laura; Pfeifer, Stefan; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Framework for the Selection of Systems Engineering Modelling Languages and Methods for Special Purpose Machinery - Wilke, Daria; Humpert, Lynn; Suwal, Pragita; Dumitrescu, Roman (Proceedings of NordDesign 2024)

A Product Lifecycle Model for the Digitally Enabled Circular Economy - Scholtysik, Michel; Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Prescriptive Analytics Data Canvas: Strategic Planning For Prescriptive Analytics In Smart Factories - Weller, Julian; Migenda, Nico; Kühn, Arno; Dumitrescu, Roman (Proceedings CPSL 2024)

Business model patterns for the circular economy - Scholtysik, Michel; Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (ISPIM Conference Proceedings)

Material Parameter Identification for a Stress-State-Dependent Ductile Damage and Failure Model Applied to Clinch Joining - Friedlein, Johannes; Böhnke, Max; Schlichter, Malte; Bobbert, Mathias; Meschut, Gerson; Mergheim, Julia; Steinmann, Paul (Journal of Manufacturing and Materials Processing)
Similar to bulk metal forming, clinch joining is characterised by large plastic deformations and a variety of different 3D stress states, including severe compression. However, inherent to plastic forming is the nucleation and growth of defects, whose detrimental effects on the material behaviour can be described by continuum damage models and eventually lead to material failure. As the damage evolution strongly depends on the stress state, a stress-state-dependent model is utilised to correctly track the accumulation. To formulate and parameterise this model, besides classical experiments, so-called modified punch tests are also integrated herein to enhance the calibration of the failure model by capturing a larger range of stress states and metal-forming-specific loading conditions. Moreover, when highly ductile materials are considered, such as the dual-phase steel HCT590X and the aluminium alloy EN AW-6014 T4 investigated here, strong necking and localisation might occur prior to fracture. This can alter the stress state and affect the actual strain at failure. This influence is captured by coupling plasticity and damage to incorporate the damage-induced softening effect. Its relative importance is shown by conducting inverse parameter identifications to determine damage and failure parameters for both mentioned ductile metals based on up to 12 different experiments.
Keywords: ductile damage; stress-state dependency; failure; parameter identification; punch test; clinching

Early childhood teachers' feedback in natural mathematical learning situations: Development and validation of a detailed category system - Aumann, Lena; Gasteiger, Hedwig; Puca, Rosa M. (Acta Psychologica)

Das Praxissemester aus Referendar:innenperspektive – Forschende Grundhaltung zwischen erster und zweiter Ausbildungsphase - Bloh, Thiemo; Homt, Martina; Bloh, Bea (Dokumentarische Professionalisierungsforschung bezogen auf das Lehramtsstudium)

Estimation of efficiency loss for stationary and moving structured packing columns using the hydrodynamic analogy approach - Ehlert, Thomas; Mamedov, Tural; Schubert, Markus; Kenig, Eugeny Y.

Aktuelle Befunde zur politischen Involviertheit von Lehramtsstudierenden in Nordrhein-Westfalen - Wehde, Janis; Bloh, Bea; Homt, Martina

Die Bedeutung von Praxisphasen für den eigenen Professionalisierungsprozess aus Referendar*innenperspektive - Bloh, Bea; Homt, Martina; Wehde, Janis

Perspektiven angehender Lehrkräfte auf Forschendes Lernen – eine qualitative Längsschnittstudie - Homt, Martina; Bloh, Bea; Wehde, Janis

Effekte eines partizipativen Lehrmoduls zur Demokratiebildung im Lehramtsstudium - Wehde, Janis (Zeitschrift für Hochschulentwicklung)
Der Beitrag untersucht die Effekte eines zwei Sitzungen umfassenden, partizipativen und themenunabhängig integrierbaren Lehrmoduls zur Stärkung der Demokratiebildungskompetenz von Lehramtsstudierenden (N = 159) in einer quasi-experimentellen Studie vom Sommersemester 2023 bis zum Sommersemester 2024. Die Ergebnisse der zweifaktoriellen Varianzanalysen mit Messwiederholungen (Pre-, Post- und Follow-up) verdeutlichen Effekte des Lehrmoduls auf die Selbstwirksamkeitserwartungen der Studierenden zur partizipativ-verfahrensorientierten Unterrichtsgestaltung und auf das methodische Wissen zur demokratischen Erarbeitung von Beurteilungskriterien in unterrichtlichen Lehr-Lern-Arrangements.

Überzeugungen von Lehramtsstudierenden zu Aspekten einer demokratischen Unterrichtsgestaltung - Wehde, Janis

Technologieakzeptanz beim Einsatz von Handhelds zur Unterstützung des Hörverstehens. Eine Datendiskussion - Hambach, Dennis

Philosophische Einmischungen. Abschiedsvorlesung, Universität Paderborn, 27.10.2023 - Peckhaus, Volker (Volker Peckhaus und Sebastian Luft: Philosophische Übergänge. Die Abschiedsvorlesung von Volker Peckhaus und die Antrittsvorlesung von Sebastian Luft im Oktober 2023)

Comparing transmission- and epi-BCARS: a round robin on solid-state materials - Hempel, Franz; Vernuccio, Federico; König, Lukas; Buschbeck, Robin; Rüsing, Michael; Cerullo, Giulio; Polli, Dario; Eng, Lukas M. (Applied Optics)
Broadband coherent anti-Stokes Raman scattering (BCARS) is a powerful spectroscopy method combining high signal intensity with spectral sensitivity, enabling rapid imaging of heterogeneous samples in biomedical research and, more recently, in crystalline materials. However, BCARS encounters spectral distortion due to a setup-dependent non-resonant background (NRB). This study assesses BCARS reproducibility through a round robin experiment using two distinct BCARS setups and crystalline materials with varying structural complexity, including diamond, 6H-SiC, KDP, and KTP. The analysis compares setup-specific NRB correction procedures, detected and NRB-removed spectra, and mode assignment. We determine the influence of BCARS setup parameters like pump wavelength, pulse width, and detection geometry and provide a practical guide for optimizing BCARS setups for solid-state applications.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Medienerziehung - Medienbildung - Herzig, Bardo; Tulodziecki, Gerhard (Handbuch Grundschulpädagogik und Grundschuldidaktik)

The individual and ecological characteristics of parental COVID-19 vaccination decisions - Hörnig, Lukas; Schaffner, Sandra; Schmitz, Hendrik (Scientific Reports)
Abstract Vaccination is a highly effective method to prevent the spread of COVID-19 and mitigate severe disease. In Germany, adult vaccination rates are relatively high at 85.5%, but rates are significantly lower for adolescents (69.6%) and children (20.0%). This discrepancy indicates that not all vaccinated parents choose to vaccinate their children. Analyzing data from a January 2022 online survey of 1,819 parents with children and adolescents, we explore the socio-economic factors influencing parents’ willingness to vaccinate themselves and their children. Our results show that individuals who vote for either side of the political extremes are less likely to vaccinate their children. This pattern is particularly strong for voters on the far right. In addition, we find that better educated parents are more likely to vaccinate both themselves and their children. Parents who vaccinate both themselves and their children demonstrate greater confidence in the vaccine’s effectiveness, while those who vaccinate only themselves are often motivated by a desire to regain personal freedoms. These insights highlight the need for targeted public health strategies to address specific concerns and improve vaccination rates among children and adolescents.